2010
DOI: 10.3399/bjgp10x514774
|View full text |Cite
|
Sign up to set email alerts
|

Can a targeted GP-led clinic improve outcomes for street sex workers who use heroin?

Abstract: Female street sex workers in the UK are often addicted to heroin, and sex work may be a result of the economic drive to fund this addiction. This study looks at outcomes of a primary care drugs treatment intervention for street sex workers who use heroin, using prescribed maintenance treatment with intensive health and psychosocial support. Thirty-four sex workers entered the study and 100% were retained in the study at 1 year. After 1 year, only 33% of participants were still sex workers. Quality of life had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 6 publications
(5 reference statements)
0
25
0
Order By: Relevance
“…One randomised controlled trial (RCT) 24 and five before and after studies 25–29 were included. There were 806 participants in the RCT and the number of participants in the observational studies ranged between 27 and 54.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One randomised controlled trial (RCT) 24 and five before and after studies 25–29 were included. There were 806 participants in the RCT and the number of participants in the observational studies ranged between 27 and 54.…”
Section: Resultsmentioning
confidence: 99%
“…The three substitute prescribing based studies 25 28 29 were in clinical settings. The oldest 1986 study 29 was in-patient based, the slightly later 1993 study 28 outpatient based and the 2010 study 25 based in a community clinic. All the non-clinical interventions were based in a community outreach setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also demonstrated significant reductions in criminal activities as determined by rates of incarceration , probability of arrests , illegal incomes , frequency of crime , and Addiction Severity Index (ASI) legal composite score . Finally, for functioning and quality of life, although less studied, the results were consistent: significant increase in productivity , significant improvement in ASI family/social composite score , and significant improvement in well‐being as determined by the Christo Inventory score .…”
Section: Resultsmentioning
confidence: 84%
“…However, it has been shown that over 48 % experienced psychological problems or depression compared to 33 % of other offenders [ 24 ]. 68 % of women in prostitution meet the criteria for Post Traumatic Stress Disorder, in the same range as victims of torture and combat veterans undergoing treatment [ 25 ].…”
Section: Introductionmentioning
confidence: 99%